The role of phonological alternation in speech production: evidence from Mandarin tone sandhi - Politzer-Ahles, Stephen (2014)
We investigate the role of phonological alternation during speech production in Mandarin using implicit priming, a paradigm in which participants respond faster to words in sets that are phonologically homogeneous than in sets that are phonologically heterogeneous. We test whether priming is obtained when words in a set share the same tones at the underlying level but have different tones at the surface level-i.e., when the set includes a word that undergoes a phonological alternation which changes the tone. Sets that are heterogeneous at the surface level (in which the heterogeneity is due to a phonological operation) failed to elicit priming, as did sets that are heterogeneous at the underlying and surface levels (in which the heterogeneity is due to the lexical representations). This finding suggests that the phonological alternation was computed before the initiation of articulation, offering evidence that the progression from underlying phonological representations to articulatory execution may be mediated online by phonological input-to-output mapping. Furthermore, sets of words that are heterogeneous only at the surface level showed a different trend than sets of words that are heterogeneous at both levels, suggesting that both the surface and underlying levels of representation play a role during speech production.